Book Review: How the Next Generation of Fiqh? - Muhammad Latif Fauzi (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2008)
Title : Muslim Legal Thought in Modern IndonesiaAuthor : R. Michael FeenerPublisher : Cambridge University PressYear : 2007Pages : 290 pp.ISBN-10 : 052187775X